Commemoration, ambivalent attachments and catharsis: David Ireland's Cyprus Avenue at the Abbey Theatre in 2016. Issue 1 (1st December 2020) - Wallace, Clare
This article analyses David Ireland's 2016 play, Cyprus Avenue, in which Eric, a middle-aged Ulster Unionist, becomes convinced that his infant granddaughter is Gerry Adams. Ireland is a Belfast-born actor and playwright whose works ‐ Can't Forget about You (2013) and Ulster American (2018) ‐ have recently generated critical acclaim and debate. Cyprus Avenue, directed by Vicky Featherstone, opened in February at the Abbey Theatre Dublin as part of the theatre's 1916 commemorative programme, before transferring to the Royal Court. With attention to the nuances of these production conditions, the ways in which Ireland's play unravels a crisis of northern Irish identity in a post-Agreement context in relation to temporality and gender are explored. Particular attention is focused on how ontological crisis is presented through dislocated, non-linear experiences of time that are enacted within a scenographically crafted space. This crisis is at once personal and impersonal ‐ a metaphor for a northern state of being ‐ and is brutally distilled in acts of violence against women. I will argue that the ideological dimensions to the affective mechanisms of the play and its performance at the Abbey Theatre in 2016 and beyond are deeply ambivalent and deserve scrutiny.